Originally Posted by

**JavaA123Chris**
the form of ax+by=c and dx+ey=f

double x = (e * d - b * f) / (a * d - b * c);

double y = (a * f - e * c) / (a * d - b * c);

}

I know this is a little late. But your program works if the equations are of the form

ax+by=e

cx+dy=f

do a little math and we get

ax+by=e <=> ax=e-by <=> x=(e-by)/a

cx+dy=f <=> c((e-by)/a)+dy=f <=> ce-cby+ady=af <=> fa-ce=y(ad-bc) <=>

y=(af-ce)/(ad-bc)

x=(e-by)/a

x=(e-b((af-ce)/(ad-bc))/a <=> x=(e/a)+(b/a)((af-ce)/(ad-bc)) <=>

x=(e/a)((ad-bc)/(ad-bc))+(b/a)((af-ce)/(ad-bc)) <=>

x=(ade-bce)/(a(ad-bc))+(baf-bce)/(a(ad-bc)) <=>

x=(ade-bce+baf-bce)/(a(ad-bc)) <=> x=(ade+baf)/(a(ad-bc)) <=>

x=(de+bf)/(ad-bc)

ad-bc=/=0